Improving Science Learning Outcomes through the TPACK Approach in Class V Students of SDN 1 Besani - Yeni Pratiwi (Universitas Sebelas Maret, 2020)
The purpose of this study in particular was to improve science learning outcomes for fifth grade students of Elementary School 1 Besani, Leksono District, Wonosobo Regency in the first semester of the 2020/2021 school year, through the application of the TPACK approach.